Decade of co-orporation achievements and perspectives - Organisation for European Economic Co-operation (Paris, 1958)
The Organisation for European Economic Co-operation comprises the following Member countries: Austria, Bel gium, Denmark, France, Germany, Greece, Iceland, Ireland, Italy, Luxembourg, the Netherlands, Norway, Portugal, Sweden, Switzerland, Turkey and the United Kingdom. The Organisation came into being with the signing of the Convention for European Economic Co operation on 16th April 1948, when Member Governments pledged themselves" to combine their economic strength, to join together to make the fullest collective use of their individual capacities and potentialities, to increase their production, develop and modernise their industrial and agricultural equipment, expand their commerce, reduce progressively barriers to trade among themselves, promote full employment and restore or maintain the stability of their economies and general confidence in their national currencies". Representatives of each of the Member countries meet daily at the O.E.E.C. headquarters, Château de la Muette, Paris, to discuss their economic problems and work out common solutions. The United States and Canada participate in all the work of the Organisation as Associate Members. Spain participates, as a full Member and on an equal footing with the Member countries, in the work of the agricultural bodies of the Organisation and is associated in its other activities. Yugoslavia is represented by an observer and like Spain also participates in the work of the European Productivity
Keywords: Economics